2013
DOI: 10.1177/0954411913501489
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis using infrared thermography of a traditional metal plate versus a carbon fibre/epoxy plate for Vancouver B1 femur fractures

Abstract: Traditional high-stiffness metal plates for Vancouver B1 femur shaft fractures below the tip of a hip implant can cause stress shielding, bone resorption, and implant loosening. This is the first study to compare the biomechanics of a traditional metal plate versus a low-stiffness carbon fibre/epoxy composite plate for this injury. A total hip replacement was implanted in two previously validated intact artificial femurs. Femurs were fitted with either a metal or composite plate and had a 5 mm fracture gap cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…The IR thermography camera employed was a Silver 420 (FLIR Systems Canada, Burlington, ON, Canada), as done previously by the authors (Figures 1(a) and 2). 9,1316 It had the following features: an image resolution of 1 MPa; an image size of 320 × 256 pixels; a built-in auto focusing 27 mm lens; and a 5 Hz to 170 Hz frame rate. It senses surface temperature changes on an object's surface due to its cyclic motion at a fixed frequency to which the IR camera has been synchronized; this is referred to as “lock-in.” The IR camera requires a minimum loading frequency of 3 to 5 Hz to achieve a cyclic temperature gradient that will produce reasonable stress map images.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IR thermography camera employed was a Silver 420 (FLIR Systems Canada, Burlington, ON, Canada), as done previously by the authors (Figures 1(a) and 2). 9,1316 It had the following features: an image resolution of 1 MPa; an image size of 320 × 256 pixels; a built-in auto focusing 27 mm lens; and a 5 Hz to 170 Hz frame rate. It senses surface temperature changes on an object's surface due to its cyclic motion at a fixed frequency to which the IR camera has been synchronized; this is referred to as “lock-in.” The IR camera requires a minimum loading frequency of 3 to 5 Hz to achieve a cyclic temperature gradient that will produce reasonable stress map images.…”
Section: Methodsmentioning
confidence: 99%
“…One reason is that stainless steel and titanium have a long established history of use for orthopaedic implants, although there is a growing interest in composite materials whose properties can be tailor-made in order to more closely match the mechanical behavior of host bone. 918 For instance, stress analysis has been done using IR thermography, strain gages, and/or FEA for a carbon fiber/polyamide 12 total hip implant, 9,10 a metal total hip implant inserted into a glass fiber/epoxy synthetic femur, 11 and a glass fiber/epoxy synthetic femur on its own. 12,13 Similarly, for bone fracture plates made from composite materials, a few studies employed IR thermography and FEA to assess unwanted “stress shielding” (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed increased bone stress with the use of composite bone plates through computer simulations or ex-vivo testing [88][89][90][91]. Kim et al [92] used the finite element method to examine the fracture gap strain distribution in a fractured tibia fixed with five different composite bone plates, and compare it to that in a fractured tibia fixed with a stainless steel plate.…”
Section: Previous Studies On Composite Fracture Fixation Devicesmentioning
confidence: 99%